Development of a participatory care model for type 2 diabetic patients to enter diabetes remission at a prototype hospital in Suphan Buri Province. - Charuchareet, Terdsak (Journal of Public Health and Innovation, 2026)
This research study is a study of the development of a participatory care model for type 2 diabetes patients to enter diabetes remission at a prototype hospital in Suphanburi Province, a case study of Dan Chang Hospital. With the intensive behavior modification program with the participation of family and patients, the aim is to create changes in health behaviors of patients with type 2 diabetes to enter into remission (Diabetes remission) with the concept of Individual and family self-management model (IFM). Or an approach that emphasizes behavioral change by the patient himself, along with support from the patient’s family and clinic personnel. The main goal is to change the perspective on diabetes treatment to focus on behavioral modification rather than drug treatment. There are thirty target groups. The research found that most of the sample patients who participated in treatment at the DM Remission clinic had positive changes in their dietary and exercise behaviors. This resulted in a significant reduction in physical factors associated with type 2 diabetes in the sample group, including body weight, waist circumference, and blood sugar levels, leading to a significant reduction in the number of the sample group of those who were able to stop taking diabetes medication, 15 cases, or 50.00 percent, were able to reduce the amount of medication taken, 14 cases, or 46.67 percent, and 1 case, or 3.33 percent, continued taking the same medication. The results of this study showed a trend towards better health behaviors among the sample group, which led them to enter remission of diabetes, leading to better health for diabetic patients. This project was achieved through the collaboration of patients, families and stakeholders, and with the success of the DM Remission Clinic at Dan Chang Hospital. The researchers therefore propose that the project be continued to expand its results to a wider target group. Furthermore, this approach should be applied to the treatment of other chronic diseases.